Analisis Ketersediaan Air Waduk Jatiluhur Sebagai Dasar Penerapan Pola Operasi Pembangkit Listrik Tenaga Air - Rumboko Kalbuardhi; Djoko Suwarno (Universitas Katolik Soegijapranata Semarang, 2018)
Analysis of the availability of water in a reservoir or mathematical approach required Jatiluhur physical, in order to predict discharge mainstay as the operating pattern of HYDROPOWER that was later used as a guide the management of the reservoir itself as initial predictions. With data-daily rainfall data of the 3 IE rain Rain Station station I, II and III, the discharge outflow, as well as the relative humidity-temperature reservoirs during the 2014 to 2016, then to estimate the availability of specialty discharge data processed with the method developed by Dr. f. j. Mock in 1973. This research is a descriptive quantitative research using secondary data obtained from relevant agencies namely Jasa Tirta II. This study aims to learn the specialty processed with debit method Mock with 15 precipitation process data daily range in year 2014 – 2016, produces a result with mainstay debit results Jatiluhur Reservoir Water Availability IE 814,399,963.00 m3/year, with 0.063341% RMSE with debit data field and serve as the basis of the operating pattern of Jatiluhur. The results of the mock model parameters where the average value of open land of outcrops (m) 39.17%, the value of the coefficient Infiltration (i) of 0.5, the Soil Moisture Capacity (SMC) of 200 mm, Flow Coefficient (K) amounted to 0.7, and Initial Storage of 100 mm.